Inflationary Implications of the Covariant Entropy Bound and the Swampland de Sitter Conjectures - Dibya Chakraborty (MDPI AG, 2021)
We present a proposal to relate the de Sitter conjecture (dSC) with the time dependence of fluxes via the covariant entropy bound (CEB). By assuming an early phase of accelerated expansion where the CEB is satisfied, we take into account a contribution from time-dependent flux compactification to the four-dimensional entropy which establishes a bound on the usual slow-roll parameters <semantics>ηH</semantics> and <semantics>ϵH</semantics>. We also show an explicit calculation of entropy from a toroidal flux compactification, from a transition amplitude of time-dependent fluxes which allows us to determine the conditions on which the bounds on the slow-roll parameters are in agreement to the dSC.